2016
DOI: 10.3390/ijerph13090889
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Adaptation to Climate Change in OECD Countries

Abstract: Climate change is a major challenge facing public health. National governments play a key role in public health adaptation to climate change, but there are competing views on what responsibilities and obligations this will—or should—include in different nations. This study aims to: (1) examine how national-level public health adaptation is occurring in Organization for Economic Cooperation and Development (OECD) countries; (2) examine the roles national governments are taking in public health adaptation; and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 79 publications
(177 reference statements)
2
47
0
2
Order By: Relevance
“…The results of this study demonstrate an increasing attention to climate change adaptation across the water management plans of Dutch water boards over time. This finding is similar to other adaptation tracking studies in different fields such as public health (Austin et al 2016) or adaptation more generally (Lesnikowski et al 2016), which also found an increase in adaptation initiatives. However, by adopting this systematic tracking approach we find more critically that adaptation is currently still at the recognition or groundwork level and progress is being made mostly when it comes to groundwork initiatives for adaptation.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study demonstrate an increasing attention to climate change adaptation across the water management plans of Dutch water boards over time. This finding is similar to other adaptation tracking studies in different fields such as public health (Austin et al 2016) or adaptation more generally (Lesnikowski et al 2016), which also found an increase in adaptation initiatives. However, by adopting this systematic tracking approach we find more critically that adaptation is currently still at the recognition or groundwork level and progress is being made mostly when it comes to groundwork initiatives for adaptation.…”
Section: Discussionsupporting
confidence: 91%
“…across the globe. Over the next several decades, Canada is predicted to increasingly experience days with temperatures over 30°C, which are strongly associated with heat-related population mortality (Austin et al 2016). In 2009, an extreme heat event in greater Vancouver caused an estimated 110 deaths (Kosatsky et al 2012); in 2010, another event in Montreal caused an estimated 106 deaths (Price et al 2013).…”
mentioning
confidence: 99%
“…Here we follow Dupuis and Biesbroek () and define adaptation policy as “... the production of outputs in forms of activities and decisions taken by purposeful public and private actors at different administrative levels and in different sectors, which deals intentionally with climate change impacts, and whose outcomes attempt to substantially impact actor groups, sectors, or geographical areas that are vulnerable to climate change” (p. 1480). In other words, we conceptualize something as adaptation policy when it is explicitly framed as such by policy makers, an approach that is consistent with most other comparative adaptation policy studies (Araos et al, ); (Austin et al, ). Given the multifaceted nature of adaptation, we unpack adaptation policy into three interrelated questions: 1) when is adaptation policy taking place (timing), 2) what kind of adaptation policy exists (action), and 3) how is this policy organized (structure).…”
Section: Administrative Traditions and Climate Change Adaptation Policymentioning
confidence: 99%